COVID-19 Pandemic and BPKIHS: our Situation, Endeavors and Future Direction - Shakya, Dhana Ratna; Mishra, Deebya Raj; Gyawali, Rajesh; Rimal, Surya Prasad; Lama, Sami; Yadav, Ajay Kumar; Nepal, Suraj; Pokharel, Bishnu; Sapkota, Nidesh (Journal of BP Koirala Institute of Health Sciences, 2020)
Rapid spread of COVID-19 infection reached Nepal in about 1 month of its first appearance in China in December 2019 and affected all spheres of life and society including health and education, like in other countries. We are unprepared for this new menace with many unknown facts and uncertainties when well developed set ups with advanced science and technology also seemed drowned. We attempt here to appraise our situation (condition, trend) and reflect on to the lessons (observations, and messages) that we draw in various major areas of the activities of B. P. Koirala Institute of Health Sciences. We become acutely aware about the adverse effects of this pandemic in its academic, service and research activities along with all other aspects. Amidst the challenges, we were forced to take steps in scattered and trial and error pattern. This pandemic has brought our deficiencies in health system into surface and is offering opportunity to review, revise and reform them. We all the stakeholders, i.e. students, patients, clients, teachers, faculties, staff and authorities are in the same boat; all need to be in healthy, balanced and functional state for fruitful travel. We have certain weaknesses, drawbacks, deficits; and some strengths that we now should realize to move ahead in this COVID era.